Urban greeen areas in the reduction of cooling loads. Simulations in the Mediterranean climate - Carola Clemente; Massimo Palme; Anna Mangiatordi; Daniele La Rosa; Riccardo Privitera (Agathón)
The fight against climate change and the right use of soil are two challenges on a global scale. The urbanization and the progressive reduction of green areas and permeable surfaces in urban settlements are amplifying some phenomena such as the increase of frequency and intensity of heatwaves and the annual average temperature, causing the growth of building energy demand. The paper examines the energy-saving potential that can be obtained by planting trees in outdoor spaces available around buildings for different urban frameworks in the Mediterranean climate. The data coming from the simulations, referred to residential sectors, expand the knowledge about the energy-environmental benefits of Green Infrastructures and are useful to guide sustainable practices of urban regeneration.